The influence of self-stigma and personality traits on attitude towards seeking professional help among college students in a faith-based university - Azares , Marielle; Mseteka , Luzungu Faith; Salvio , Rafnielle Joy; Tobias , Ma. Ellaine; Guanco , Rhalf Jayson; Canesares , Cutie; Balila , Jolly; Fajanilan, Levy (12th International Scholars Conference 2025, 2026)
This study explores the influence of self-stigma and personality traits on the attitude toward seeking professional psychological help among college students in a faith-based university. Data was collected from 405 participants (32 from a pilot study and 373 from the main study) using both online and hardcopy questionnaires (Google Forms). Descriptive and correlational analysis were conducted using SPSS, and the suggested mediation model was validated using structural equation modelling. The respondents' low levels of self-stigma were revealed by the findings. Regarding their attitude towards seeking help, the students exhibit a good inclination to seek help and an uncertain indifference to stigma and psychological openness. In contrast, extraversion and openness were high, while neuroticism, agreeableness, and consciousness were considered uncertain. It was discovered that self-stigma predicted attitudes toward seeking psychological help. Agreeableness was revealed to be the best predictor of attitudes towards obtaining psychological assistance. In terms of gender, age, and college, it was discovered that women were more likely to be positive about asking for help, and that students in the arts, education and science colleges were more willing to do so. Personality qualities and help-seeking attitudes are positively correlated, whereas self-stigma and attitudes are negatively correlated. Personality traits were found to partially mediate the relationship between self-stigma and attitude toward seeking psychological help.